2018
DOI: 10.3390/cells7120238
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Quality Control Mechanisms and the PHB (Prohibitin) Complex

Abstract: Mitochondrial functions are essential for life, critical for development, maintenance of stem cells, adaptation to physiological changes, responses to stress, and aging. The complexity of mitochondrial biogenesis requires coordinated nuclear and mitochondrial gene expression, owing to the need of stoichiometrically assemble the oxidative phosphorylation (OXPHOS) system for ATP production. It requires, in addition, the import of a large number of proteins from the cytosol to keep optimal mitochondrial function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 130 publications
(214 reference statements)
3
37
0
Order By: Relevance
“…PHB is a mitochondrial protein which has emerged as an important modulator of neuronal survival in different injury models (Zhou et al, 2012; Hernando-Rodríguez and Artal-Sanz, 2018). PHB localizes to the inner membrane of mitochondria acting as a chaperone protein, but is also found in the nucleus, where it negatively regulates transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHB is a mitochondrial protein which has emerged as an important modulator of neuronal survival in different injury models (Zhou et al, 2012; Hernando-Rodríguez and Artal-Sanz, 2018). PHB localizes to the inner membrane of mitochondria acting as a chaperone protein, but is also found in the nucleus, where it negatively regulates transcription.…”
Section: Discussionmentioning
confidence: 99%
“…PHB is a pleiotropic multifaceted protein and an essential factor in mitochondrial homeostasis, biogenesis, degradation, and response to stress (Peng et al, 2015; Ande et al, 2017; Hernando-Rodríguez and Artal-Sanz, 2018). In mitochondria, PHB acts as a scaffold protein and is thus crucial for regulation of mitochondrial architecture, mitochondrial dynamics, morphology, and biogenesis, and furthermore stabilizes the mitochondrial genome (Merkwirth et al, 2012; Peng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an increased level of the PHB complex has been reported under UPR mt activation as depending on imbalance in the synthesis of mitochondrial- and nuclear-encoded mitochondrial proteins, in mammals [60] and C. elegans [13], or on accumulation of unassembled subunits of respiratory chain, in yeast [61]. In C. elegans , it is also reported that the lack of PHB induces a strong UPR mt activation (reviewed in [62]). This enforces the role of PHBs in the mitochondrial protein quality control.…”
Section: Role Of Prohibitins In Unfolded Protein Response (Uprmt)mentioning
confidence: 99%
“…Kathiria et al [62] show that PHB1 knockdown generates reactive oxygen species, mitochondrial depolarization, and induced autophagy. In Hernando-Rodríguez and Artal-Sanz [63], several phenotypes of PHB are reviewed, including the role of PHB in mitochondrial stability. PHB has also been implicated in the inflammatory response in both the lung and gut [63,64].…”
Section: Nonstructural Protein 2 (Nsp2)mentioning
confidence: 99%